African Swine Fever Virus Exhibits Distinct Replication Defects in Different Cell Types - Yanni Gao; Tingting Xia; Juan Bai; Lujie Zhang; Xiaolin Jiang; Xing Yang; Keshan Zhang; Ping Jiang (Viruses, 2022)
African swine fever virus (ASFV) causes one of the most devastating diseases affecting pigs and wild suids, a worldwide epizootic situation exacerbated in recent years due to the lack of vaccine or effective treatment. ASFV has a restricted cell tropism, and is prone to replicate in porcine monocytes and alveolar macrophages with high efficiency. Here, the replication capabilities of ASFV were examined in swine pulmonary alveolar macrophages (PAMs) and compared with 3D4/21, PK-15, MA-104 and Marc-145 cell lines using PCR, qPCR and Western blot with monoclonal antibodies against the viral p30 and p72 proteins. The results showed that ASFV has a variety of infection characteristics in PAMs and showed four cell lines with distinct defects during virus early transcription-translation, genome replication and late protein synthesis. Furthermore, an antiviral role of the stress granule pathway was revealed against ASFV, and ASFV infection inhibited stress granule formation in PAMs but not 3D4/21. These results will help to deepen our knowledge on ASFV infection and to develop ASFV susceptible cell lines.